SOCIAL HOUSING IN UKRAINE: CHALLENGES AND PROSPECTS - ZAPOTOTSKA, Viktoriia; PANKIV, Andrii; SHPAK, Danila (Bulletin of Taras Shevchenko National University of Kyiv, Geography, 2025)
Background. The concept of social housing is a recent one, but as an idea, it dates back to the First Industrial Revolution. The modern definition of social housing, while varying from country to country, includes key features such as targeting groups of population with limited financial resources and requiring financial support from the state or private sector. Housing is crucial in everyday life, closely linked to a sense of security, control over life, stability, and health; housing circumstances play a key role in the formation and functioning of a social unit. Methods. The study used the method of analysing theoretical literature, as well as reports and statistics, historical and descriptive methods, comparative analysis, and method of generalization. Results. The article presents the results of a study of the concept of ’social housing’, the current state, problems, and prospects of social construction. The study is based on the analysis of data collected in theoretical literature, as well as reports and statistic databases describing social housing. The study analyses the formation of social housing and the stages of its development and compares the experiences of other countries and Ukraine. Examples of successful implementation of social housing programmes, foreign and Ukrainian practices were collected. The quantitative characteristics of social housing needs, the current situation, and programs aimed at providing housing for vulnerable groups are described. Conclusions. It is found that Ukrainian legislation does not regulate the issues of social, temporary, and affordable housing, there are no clear mechanisms for providing the population with social housing and there is a critical shortage of it, even though there is a great demand for it. It is proved that the housing market requires clear legislative regulation and the creation of an effective housing policy in the country. The findings highlight the main problems of social housing, especially among IDPs, show options for meeting housing needs, and can contribute to better implementation of housing policy and overcoming the housing crisis.